2004
DOI: 10.1146/annurev.phyto.41.052002.095701
|View full text |Cite
|
Sign up to set email alerts
|

CHEMICAL BIOLOGY OF MULTI-HOST/PATHOGEN INTERACTIONS: Chemical Perception and Metabolic Complementation

Abstract: The xenognostic mechanisms of two multi-host pathogens, the causative agent of crown gall tumors Agrobacterium tumefaciens and the parasitic plant Striga asiatica, are compared. Both organisms are general plant pathogens and require similar information prior to host commitment. Two mechanistic strategies, chemical perception and metabolic complementation, are used to ensure successful host commitment. The critical reactions at host-parasite contact are proton and electron transfer events. Such strategies may b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
62
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 101 publications
2
62
0
Order By: Relevance
“…The constant and rapidly changing evolutionary tensions between intimately associated organisms may be most developmentally and metabolically dynamic in the sessile parasitic plants where chemical and tactile cues direct lifecycle phases [2]- [4]. The host-derived cues that mediate both acute and chronic developmental decision-making events are known as xe- Many of these xenognosins and their analogues are now readily available, so these transitions can be easily and effectively managed under laboratory conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The constant and rapidly changing evolutionary tensions between intimately associated organisms may be most developmentally and metabolically dynamic in the sessile parasitic plants where chemical and tactile cues direct lifecycle phases [2]- [4]. The host-derived cues that mediate both acute and chronic developmental decision-making events are known as xe- Many of these xenognosins and their analogues are now readily available, so these transitions can be easily and effectively managed under laboratory conditions.…”
Section: Introductionmentioning
confidence: 99%
“…1). [1][2][3][4] As these parasites are responsible for billions in lost agricultural yields worldwide and a major source of malnutrition and poverty throughout the developing world, there has been considerable interest in developing new strategies to interpret and disrupt signaling. The recent elucidation of a new role for reactive oxygen species (ROS)-molecules traditionally associated with defense-in host selection by parasitic angiosperms underscores the complex interplay between signaling events, and may open new strategies for intervention.…”
Section: "Tell Me What You Eat and I Will Tell You Who You Are"mentioning
confidence: 99%
“…Previous results had suggested that the accumulation of the p-benzoquinone xenognosins, which regulate the transition between vegetative growth and development of the host attachment organ known as the haustorium, were dependant on parasite-derived H 2 O 2 . [1][2][3][4] In the recent study, fluorescence and transmission electron microscopies successfully defines both the cellular site of oxidant production as well as the sensitive feedback regulation by the xenognosin. 5 Indeed, ROS production by the parasite appeared insufficient to cross-link cell wall components or activate apoptosis in either plant, but was sufficient to generate the necessary p-benzoquinone xenognosins from host cell walls.…”
Section: "Tell Me What You Eat and I Will Tell You Who You Are"mentioning
confidence: 99%
See 1 more Smart Citation
“…The specific composition of phenolic compounds secreted by wounded plants is thought to underlie the host specificity of some Agrobacterium strains. Besides phenolic compounds, other inducing factors include aldose monosaccharides, low pH, and low phosphate (Brencic & Winans, 2005;McCullen & Binns, 2006;Palmer et al, 2004). However, phenols are indispensable for vir gene induction, whereas the other inducing factors sensitise Agrobacteria to phenols.…”
mentioning
confidence: 99%